Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

destineec

  • 2 years ago

Divide f(x) by d(x), and write a summary statement in the form indicated. f(x) = x^4 + 5x^3 - 2x^2 + 5x - 3; d(x) = x^2 + 1 f(x) = (x2 + 1)( x2 + 5x - 3) f(x) = (x2 + 1)( x2 + 5x - 3) - 15x - 9 f(x) = (x2 + 1)( x2 - 5x - 3) - 15x - 9 f(x) = (x2 + 1)( x2 - 5x - 3)

  • This Question is Open

    Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy